Euplotes petzi Wilbert and Song 2008 - Yeo, Jeong Hyeon; Jung, Pablo Quintela-Alonso and Jae-Ho (Zenodo, 2023)
4. Euplotes petzi Wilbert and Song, 2008 (Fig. 4) Material examined. Marine water (salinity 28‰) collected from West Sea, Janghang-eup, Seocheon-gun, Chungcheongnam-do, Korea (36°00′55″N, 126°39′49″E) on January 21, 2021. A B C Diagnosis. Body size 38.2-46.2 × 25.3-36.7 μm (on average 42.6 × 29.9 μm) after protargol impregnation, shape ellipsoidal; macronucleus hook-shaped, with one spherical micronucleus attached; 35-45 adoral membranelles; 10 frontoventral, 5 transverse, 2 caudal and 2 marginal cirri; invariably 6 dorsal kineties, of which the middle kinety composed of about 8-10 dikinetids; dorsal argyrome pattern in double- patella type. Distribution. King George Island (Wilbert and Song, 2008) and Korea (present study). Remarks. The morphology of the Korean and King George Island populations of Euplotes petzi (Wilbert and Song, 2008) is mostly similar except cell size (38-46 × 25-37 μm, and 50-80 × 30-50 μm). A distinctive morphological feature of this species is the narrow separation between the two marginal cirri compared to other Euplotes species. Di Giuseppe et al. (2014) improved the morphological characterization of E. petzi and used SSU rDNA gene sequences to relate this species to E. sinicus Jiang et al. , 2010b as the deepest branch at the base of the Euplotes phylogenetic tree. Moreover, their investigation revealed notable similarities between these two species in terms of the cell size and key characteristics. Voucher slides. One slide with protargol-impregnated specimens (NNIBRPR25661) and one slide with wet silver nitrate-impregnated specimens (NNIBRPR25662) were deposited at the Nakdonggang National Institute of Biological Resources. Published as part of Yeo, Jeong Hyeon & Jung, Pablo Quintela-Alonso and Jae-Ho, 2023, New record of five Euplotes species (Protozoa, Ciliophora) collected from South Korea, pp. 203-211 in Journal of Species Research 12 (3) on pages 206-207, DOI:10.12651/JSR.2023.12.3.203, http://zenodo.org/record/13139732